2014
DOI: 10.4314/tjpr.v13i4.19
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of the Aerial Parts of Some <i>Centaurea</i> Species in Elazig, Turkey

Abstract: Purpose: To evaluate the fatty acid composition of six Centaurea species, viz, Centaurea behen, C. saligna, C. depressa, C. urvillei subsp. urvillei, C. urvillei subsp. hayekiana and C. aggregata

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…abbreviate and C. babylonica) were analyzed for their fatty acids composition and although the major compounds were similar to all the species (linoleic, palmitic, linoleic and α-linolenic acid) significant differences in fatty acids profile were observed. Similarly, Erdogan et al [87] and Tekeli et al [88,89] studied the aerial parts of various endemic to Turkey Centaurea species and reported a significant variation in the fatty acids profile. Finally, apart from leaves the flowers of some Centaurea species are edible presenting a different fatty acids profile compared to leaves [90,91].…”
Section: Fatty Acids Compositionmentioning
confidence: 91%
“…abbreviate and C. babylonica) were analyzed for their fatty acids composition and although the major compounds were similar to all the species (linoleic, palmitic, linoleic and α-linolenic acid) significant differences in fatty acids profile were observed. Similarly, Erdogan et al [87] and Tekeli et al [88,89] studied the aerial parts of various endemic to Turkey Centaurea species and reported a significant variation in the fatty acids profile. Finally, apart from leaves the flowers of some Centaurea species are edible presenting a different fatty acids profile compared to leaves [90,91].…”
Section: Fatty Acids Compositionmentioning
confidence: 91%
“…stepposa are used as foodstuff and eaten while fresh 11,12 . The uses of its species in traditional medicine could be causes of the high number of studies on members of the genus Centaurea [13][14][15] . However, there is no report in the literature on the phytochemical profile and biological activities of C. urvillei subsp.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that seed oil and plant aerial parts oil compositions differ in Centaurea species. In a recent study, it has been reported that oleic acid levels varied from 3.4% to 25.12% in six different Centaurea species' arial parts [35]. Oleic and linoleic acid intake have been encouraged by nutritionists and the medical professions because of their ability to lower blood cholesterol levels [36].…”
Section: Fatty Acid Composition Of C Albonitens and C Balsamita Seementioning
confidence: 99%